A Moderator Analysis of the Relationship Between Mental Health Help-Seeking Attitudes and Behaviours among Young Adults - Beatie, Brooke E.; Stewart, Donald W.; Walker, John R. (Canadian Journal of Counselling and Psychotherapy, 2016)
To explore how psychological factors influence mental health help seeking among young adults, an online questionnaire was administered to 486 participants assessing their mental health attitudes and experiences, symptom acuity, and psychological fortitude in relation to mental health help seeking. Results showed that help-seeking attitudes were predicted by self-stigma, fortitude, symptom acuity, and level of familiarity with mental health problems. However, not all of these variables directly influenced help-seeking behaviour. Moderator analyses indicated that self-stigma, level of familiarity with mental health problems, and symptom acuity moderated the relationship between help-seeking attitudes and behaviours. Implications for increasing help seeking among young adults are discussed.